A comparative analysis of Turkish and European Union environmental legislation regarding cleaner (sustainable) production concept. (1st January 2011) - Ulutas, Ferda; Alkaya, Emrah; Böğürcü, Merve; Demirer, Göksel N.
The term cleaner (sustainable) production has been cited in many policy and strategy documents of the top level agency/institutions on science, technology, development, etc., in Turkey for over a decade. However, it is not sufficiently known and applied except its energy efficiency aspect in Turkey. So as to overcome this deficiency, the Ministry of Environment and Forestry supported the project 'Determination of the Framework Conditions and Research-Development Needs for the Dissemination of Cleaner (Sustainable) Production Applications in Turkey' which was carried out in 2009 by TTGV and Göksel N. Demirer, as the consultant. This paper summarises this analysis which was one of the outcomes of this project.